Tsunami Flow Characteristics And Design Load Equations For Residential Buildings Located At Malaysian Coastline - Moon, Wei Chek (2019)
Tsunami-induced damage of building has been evidentially demonstrated by the post-tsunami surveys worldwide, including Malaysia. Up to present, buildings located at Malaysian coastline are not tsunami proof and are susceptible to the future tsunami threat. Motivated by the above concerns, hydraulic experiment and numerical simulation were conducted to evaluate the tsunami impact on a Malaysian typical single-storey residential building at a reduced scale of 1:50. Nominal wave conditions with wave-overtopping and non-overtopping cases were tested to study its effects in combination with each building model type with and without opening. Hydraulic experimental results demonstrated that the building model with a gabled roof had a 12% increment and 52% reduction of the force induced on the front and back faces, respectively. As the tsunami wave flowed through a building model, the induced force on an internal wall’s front face increased up to 50% as the front opening size increased from 15% to 35%, whereas a decrement up to 30% was demonstrated as the internal wall moved from 60 mm to 180 mm. For the back face of an internal wall, the force interrelated with each parameter of front and back opening and the internal wall configuration. For the worst scenario where an internal wall was positioned near a smaller back opening, the back face force on the internal wall increased up to 100% as the front opening increases from 15% to 35%. For tsunami modelling, a three-dimensional higher-order numerical model (VSIAM3+TM) was developed, in view of challenges in simulating the tsunami wave propagation and its impulsive motion during impact on a vertical wall. Based on the combinational approach from the experimental and numerical analysis, empirical equations for wave pressure estimation on the front and back faces of a building were first proposed. For the estimation of tsunami impact on an internal wall’s front face, a new measure of the wake clearance angle (β) was proposed, considering the effect of the front opening and the internal wall configuration. Conversely, a dimensionless factor of front to back opening ratio was proposed, considering the effect of both front and back openings to determine the maximum force on an internal wall’s back face. As there were paucity studies on the tsunami impact on an internal wall, the findings in this study were believed to provide new insight towards the development of the design of a tsunami-resilient building.